Edukasi Penyelaman Aman bagi Nelayan Pesisir Montong Lombok Barat - Eustachius Hagni Wardoyo; Yoga Pamungkas Susani; Decky Aditya Zulkarnaen; Ida Ayu Eka Widiastuti; Bayu Tirta Dirja; Dini Suryani; Ika Primayanti; Muhammad Ghalvan Sahidu; Didit Yudhanto; Ardiana Ekawanti (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Traditional diver diving activities look for fish by archery underwater frequently do not pay attention to safety aspects, so there is an increasing risk of causing diving injuries. Diving injuries are preventable injuries, if safe diving guidelines are followed and obeyed. Diving injuries symptoms can be mild to severe, so education about prevention and recognition of disease disorders that can occur due to diving is being given. The community service is carried out in two simultaneous activities: diving safety lectures and general medical examination. The participants, 30 participants for general medical examination, and 4 participants for traditional divers. Of the 30 participants for general medical examination, it was predominantly female (18/30), with an age range of 4-60 years with a median age of 37 years. The most common diseases that are complained of are upper respiratory tract infections (ARI) (8/30), skin complaints (6/30), hypertension (6/30), diabetes (4/30), headaches (3/30), diarrhea (1/30), musculoskeletal complaints (1/30) and toothache (1/30). Education is carried out to all participants. The media used were a slide projector and x-banner. Four traditional divers comes with 3 Decompression sickness and 1 barotrauma. Questions coverage diving preparation, Diving techniques and do's and don't's after diving. The community service went well with 34 enthusiastic participants filled by questions. Three most common diseases being ARI, skin complaints and hypertension and diving injuries of decompression sickness and barotrauma.